2019
DOI: 10.1590/s1984-296120180087
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mini-FLOTAC and Fill-FLOTAC for rapidly diagnosing parasitic infections in zoo mammals

Abstract: Animals reared in restricted environments are highly susceptible to gastrointestinal infection by helminths and protozoa and therefore zoos are characterized as being parasite-rich environments. Successful implementation of control programs of these parasites in zoo environment depends upon precise and rapid diagnosing of gastrointestinal infections. The aim of this study was to demonstrate the role of the Mini-FLOTAC technique in combination with Fill-FLOTAC for rapidly diagnosing parasitic infections in zoo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
2
11
1
Order By: Relevance
“…Over the past seven years, Mini-FLOTAC (MF) has been used in routine parasitological diagnosis in several animal species, and most of the studies concluded that this technique is a good alternative to the traditional McMaster technique, allowing simultaneous identification of helminth eggs and coccidia oocysts with relatively higher sensitivity, accuracy and precision. Established in the Unit of Parasitology and Parasitic Diseases of the Department of Veterinary Medicine and Animal Production (University of Naples Federico II, Naples, Italy), the manufacturer proposes three MF protocols for animals, namely for small animals (e.g., dogs and cats), herbivores (e.g., ruminants and horses) and exotic species (e.g., birds and reptiles), which involve different fecal dilutions and detection limits [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past seven years, Mini-FLOTAC (MF) has been used in routine parasitological diagnosis in several animal species, and most of the studies concluded that this technique is a good alternative to the traditional McMaster technique, allowing simultaneous identification of helminth eggs and coccidia oocysts with relatively higher sensitivity, accuracy and precision. Established in the Unit of Parasitology and Parasitic Diseases of the Department of Veterinary Medicine and Animal Production (University of Naples Federico II, Naples, Italy), the manufacturer proposes three MF protocols for animals, namely for small animals (e.g., dogs and cats), herbivores (e.g., ruminants and horses) and exotic species (e.g., birds and reptiles), which involve different fecal dilutions and detection limits [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the goat species, the Mini-FLOTAC presented a better performance in the detection of any type of egg. One of the advantages compared to other methods is the use of different flotation solutions, increasing the egg recovery percentages in all samples (Capasso et al, 2019). The Mini-FLOTAC showed higher sensitivity for detection of Strongyloidea eggs (98.37% and 96.77%) for goats and sheep, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of the mini-FLOTAC technique is that it permits work with fixed fecal samples. Formalin or any preservative can be added and the samples stored for further testing [31] . This allows the possibility of examining the samples on different days and improves the quality control process.…”
Section: Discussionmentioning
confidence: 99%